Biosorption‐based dispersive liquid–liquid microextraction combined with polypyrrole‐coated magnetic nanoparticles as an effective sorbent for the extraction of ibuprofen from water samples using magnetic solid‐phase extraction. Issue 21 (21st August 2017) - Haeri, Seyed Ammar; Abbasi, Shahryar; Sajjadifar, Sami
Abstract: In this paper, biosorption‐based dispersive liquid–liquid microextraction (BioDLLME) in combination with magnetic solid‐phase extraction (MSPE) has been developed as a sample pretreatment method with high enrichment factor for the sensitive determination of ibuprofen in water samples. At first, magnetic Fe3 O4 /polypyrrole nanoparticles were synthesized and employed as sorbent for the MSPE of ibuprofen. After the elution of the desired compound from the sorbent by using methanol, BioDLLME technique was performed on the obtained solution. After MSPE, the eluent of MSPE was used as the disperser solvent for BioDLLME, so that the extra preconcentration factor could be achieved. The properties of the prepared magnetic sorbent were characterized using field emission scanning electron microscopy, Fourier transform infrared spectroscopy and X‐ray diffraction methods. Experimental parameters affecting the extraction efficiency were studied and optimized. Under optimum conditions, the enrichment factor was 274. The linear dynamic range and limit of detection are 0.25–80 and 0.083 μg/L, respectively. The relative standard deviations for six replicate measurements are 3.82%.